Descompactação mecânica e biológica: efeitos nas propriedades físicas e no carbono orgânico do solo - Pan, Renan (2020)
Soil compaction is generally considered negative in a crop management system once it can reduce the water infiltration, the soil aeration and gas exchanges, increasing the surface runoff and erosion, affecting the crops development and their productivity. The soil organic carbon content is directly related to the soil physical properties, being that increases in its concentration are capable of reducing the soil potential to be compacted once it increases its resistance to deformation by increasing its elasticity. The objectives of the present work were to evaluate the effect of soil management: mechanical, biological and its association in autumn / winter cultivation on physical soil properties and soybean productivity in succession; evaluate the effects of management: no tillage, mechanical and biological soil loosening in the soil organic carbon content (SOC) and its fractions. The experiment was carried in the experimental area Alcebíades Luís Orlando located in Entre Rios do Oeste – PR, during 2018 to 2019. The experiments design was of randomized block (RBD) in time split-plot with four replicates. The first factor consisted in 5 management systems: Management 1 – forage radish + black oats followed by chiseling; Management 2 – forage radish + black oat without chiseling; Management 3 – maize second crop followed by a chiseling after its harvest; Management 4 – maize second crop followed by buckwheat in succession; Management 5 – maize second crop without chiseling (control). The collections to determine the physical properties were carried in three times March/2018, October/2018 and March/2019; and for the evaluation of the carbon content and its fractions only two times October/2018 and March/2019. The disturbed and undisturbed samples were collected in three depths: 0,05-0,10 m, 0,10-0,15 m and 0,15-0,20 m. It was evaluated soil bulk density, macroporosity, microporosity and total porosity, besides the dry matter apported to the soil, soil coverage and the soybean production components. For the evaluation of the managements on the soil organic carbon it was evaluated the total organic carbon (TOC), non-humified carbon (NHC) and the humified carbon fractions fulvic acid (FA), humic acid (HA) and humin (HUM), besides the FA/HA and AE/HUM (alkaline extraction) ratios. The mechanical and biological soil loosening improved the macroporosity and total porosity in some depths. However, they did not remain and returned to the area initial conditions. The soil porosity increased when the chiseling was associated to the cover crops forage radish + black oat. The crop forage radish + black oat produced the highest amount of dry matter on the soil surface. The chiseling after the maize second crop decreased the percentage of soil cover, compromising the no-till quality. The soybean yield was not influenced by the managements. In the present study there were decreases in the TOC, FA, HA and HUM after the soybean crop in all depths tested. Showing that in regions with high temperatures and rainfalls there is losses in carbon and its fractions with the time. The total organic carbon in the area with forage radish in consortium with black oat in the 0,15-0,20 m depth with soybean in succession was higher than in the area with maize/buckwheat. The area with soybean, which had maize harrowed after its harvest, had the highest humin content in the 0,05-0,10 m and 0,15-0,20 m depths.